The Gut Microbiota of Newborn Calves and Influence of Potential Probiotics on Reducing Diarrheic Disease by Inhibition of Pathogen Colonization - Fan, Peixin; Kim, Miju; Liu, Grace; Zhai, Yuting; Liu, Ting; Driver, Joseph Danny; Jeong, Kwangcheol C. (Frontiers in Microbiology, 2021)
Calf diarrhea is one of the most concerning challenges facing both the dairy and beef cattle industry. Maintaining healthy gut microbiota is essential for preventing gastrointestinal disorders. Here, we observed significantly less bacterial richness in the abnormal feces with watery or hemorrhagic morphology compared to the normal solid feces. The normal solid feces showed high relative abundances of Osllospiraceae, Christensenellaceae, Barnesiella, and Lactobacillus, while the abnormal feces contained more bacterial taxa of Negativicutes, Tyzzerella, Parasutterella, Veillonella, Fusobacterium and Campylobacter. Healthy calves had extensive bacterial-bacterial correlations, with negative correlation between Lactobacillus and potential diarrheagenic E. coli-Shigella, but not in the abnormal feces. We isolated Lactobacillus species (L. reuteri, L. johnsonii, L. amylovorus, and L. animalis), with L. reuteri being the most abundant, from the healthy gut microbiota. Isolated Lactobacillus strains inhibited pathogenic strains including E. coli K88 and Salmonella Typhimurium. These findings indicate the importance of a diverse gut microbiota in newborn calf’s health and provide multiple potential probiotics that suppress pathogen colonization in the gastrointestinal tract to prevent calf diarrhea.